CT and MRI characteristics for differentiating mediastinal Müllerian cysts from bronchogenic cysts. Issue 12 (December 2019) - Kawaguchi, M.; Kato, H.; Hara, A.; Suzui, N.; Tomita, H.; Miyazaki, T.; Iwata, H.; Matsuo, M.
Abstract : AIM: To evaluate how computed tomography (CT) and magnetic resonance imaging (MRI) characteristics can be used to differentiate immunohistochemically confirmed mediastinal Müllerian cysts (MMCs) from bronchogenic cysts (BCs). MATERIALS AND METHODS: Sixteen patients with histopathologically and immunohistochemically confirmed mediastinal cysts (four with MMCs and 12 with BCs) were included in this study. CT and MRI images were reviewed retrospectively and the location, size, CT attenuation, and MRI signal intensity of the two pathologies were compared. RESULTS: On review of CT images, cysts could be located to the anterior mediastinum in four BCs, middle mediastinum in three MMCs and seven BCs, and posterior mediastinum in one MMC and one BC. Contact with a vertebral body was observed in 4/4 MMCs (100%) and 6/12 BCs (50%). The ratios of minimum-to-maximum diameter (0.57±0.09 versus 0.74±0.11, p <0.01), CT attenuation (7.8±6 versus 44.3±12 HU, p <0.01), and cyst-to-spinal cord signal intensity ratios (SIRs) on T1-weighted images (0.56±0.2 versus 1.31±0.4, p <0.01) were significantly lower for MMCs than BCs. No significant differences in maximum diameter, minimum diameter, and SIRs on T2-weighted images were found between MMCs and BCs. CONCLUSION: In characterising mediastinal cysts in a middle-aged female patient, contact with a vertebral body, flattened configuration, hypodensity on CT, and hypointensity compared to spinal cord on T1-weighted images are features that are specific to MMCs. Highlights: Contact with a vertebral body was observed in all MMCs. The ratios of minimum-to-maximum diameter were lower for MMCs than BCs. CT attenuation within cysts were lower for MMCs than BCs. Cyst-to-spinal cord SIRs on T1WI were lower for MMCs than BCs.